Bats assemblage and lunar phase effect on bat activity at mixed dipterocarp forest, Gunung Gading National Park, Sarawak, Borneo - Mohd-Ridwan A.R.,; Nurul Farah Diyana Ahmad Tahir,; Mohamad Haikal Eshak,; Csorba, Gábor; Görföl, Tamás; Faisal Ali Anwarali Khan,; Jayasilan Mohd-Azlan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bat surveys at Gunung Gading National Park (GGNP) were conducted for 29 non-consecutive nights, which consisted of five separate sampling sessions from November 2011 until November 2015. A total of 378 individuals representing 36 species from six families were captured, from an accumulated effort of 435 trapping nights. This corresponds to approximately 39% (n=36) of the total species recorded in Borneo. The most commonly captured species in GGNP for insectivorous bats was Rhinolophus affinis (20.1%), whereas for frugivorous bats Penthetor lucasi (14.3%) dominated the capture. Species accumulation curve reached asymptote on the 24th sampling night suggesting that sampling saturation has been achieved for the trapping sites studied here. The species diversity (H’= 2.75) showed relatively high diversity of bat species in the park compared to other actively surveyed sites in western Sarawak including Bako National Park (Bako NP), Kubah National Park (Kubah NP) and Mount Penrisen (Mt Penrisen). This was further supported through rarefaction analysis showing that GGNP has largest value of estimated species compared to other actively surveyed sites in western Sarawak. Lunar phase and bat capture rate correlation analysis showed that there is no statistically significant relationship between lunar phase and the bat capture rate at GGNP. This suggests that bat activity reported here were not affected by moonlight. The results from these surveys provided the most comprehensive list of bats for GGNP. Our study highlights the importance of GGNP as an important habitat for bat conservation including the rare bat species found in Borneo, Phoniscus atrox.